Therapeutic mechanism of Curcuma aromatica Salisb. rhizome against coronary heart disease based on integrated network pharmacology, pharmacological evaluation and lipidomics - Fei, Chenghao; Ji, De; Tong, Huangjin; Li, Yu; Su, Lianlin; Qin, Yuwen; Bian, Zhenhua; Zhang, Wei; Mao, Chunqin; Li, Lin; Lu, Tulin (Frontiers in Pharmacology, 2022)
Curcuma aromatica Salisb. rhizome (CASR) has multifunctional characteristics worldwide and a long history of use as a botanical drug with. Currently, it is often used clinically to treat coronary heart disease (CHD) caused by blood stasis syndrome. However, the therapeutic mechanism of CASR in the treatment of CHD remains poorly understood. In study, the main chemical constituents of CASR were analyzed using UPLC-Q-TOF-MS/MS. Then, its potential therapeutic mechanism against CHD was predicted. Subsequently, pharmacological evaluation was performed using CHD rat model. Finally, a lipidomics approach was applied to explore the different lipid metabolites to verify the regulation of CASR on lipid metabolism disorders in CHD. A total of 35 compounds was identified from CASR. Seventeen active components and 51 potential targets related to CHD were screened by network pharmacology, involving 13 key pathways. In vivo experiments showed that CASR could significantly improve myocardial infarction, blood stasis, and blood lipid levels and regulate the PI3K/AKT/mTOR signaling pathway in CHD rats. Lipidomics further showed that CASR could regulate abnormal sphingolipid, glycerophospholipid, and glycerolipid metabolism in CHD rats. The therapeutic mechanism of CASR against CHD was initially elucidated and included the regulation of lipid metabolism. Its effects may be attributed to active ingredients, such as curzerene, isoprocurcumenol, and (+)-curcumenol. This study reveals the characteristics of multi-component and multi-pathway of CASR in the treatment of CHD, which provides a basis for the follow-up development and utilization of CASR.